[PP.15.01] VISIT-TO-VISIT BLOOD PRESSURE VARIABILITY IN UNCOMPLICATED AND COMPLICATED ARTERIAL HYPERTENSION. (September 2016) - Troitskaya, E.; Kotovskaya, Y.; Kobalava, Z.
Abstract : Objective: Visit-to-visit blood pressure variability (BPV) is associated with adverse cardiovascular outcomes in different patients' populations. Mechanisms of visit-to-visit BPV in different groups of patients have not been determined yet. The aim of our study was to assess visit-to-visit systolic BPV in patients with uncomplicated controlled arterial hypertension (AH) and patients with controlled AH and stable coronary heart disease (CHD) or heart failure (HF) with reduced ejection fraction. Design and method: In retrospective study we assessed 3 groups of patients with controlled AH. Group 1 included 52 patients with uncomplicated AH (20 men, age 58, 9 ± 9, 0 yrs) who achieved target BP on RAAS-inhibitor/amlodipine combination. Group 2 included 40 pts with stable CHD (28 men, age 69, 2 ± 5, 9 yrs). Group 3 included 100 pts with HF with reduced EF (80 men, age 64, 4 ± 9, 3yrs, mean EF 32, 3 ± 4, 3%). Pts in groups 2 and 3 received stable therapy for CHD and HF. BP was measured with a validated oscillometric device. Visit-to-visit BPV was calculated as SD for 5–7 visits during 8–18 months of stable therapy. p < 0, 05 was considered significant. Results: At first evaluated visit BP in group 1 was 126, 4 ± 7, 6/76, 7 ± 7, 2 mmHg, in group 2 - 125, 5 ± 7, 5/75, 2 ± 8, 8 mmHg, in group 3 - 127, 6 ± 15, 1/77, 9 ± 8, 3 mmHg. At final evaluated visit BP was 123, 7 ± 9, 7/76, 8 ± 6, 7mmHg, 124, 2 ± 13, 4/72 ± 8, 5 mmHg and 123, 6 ± 13, 6/74, 8 ± 8, 9 mmHg, respectively. Despite stable levels of BP, BPV on stable therapy varied in wide range in all groups: 1, 8–16, 8 mmHg, 0, 7–23, 3 mmHg, 2, 3–20, 0 mmHg for systolic BPV, respectively and 1, 0–11, 4 mmHg, 0–17, 9 mmHg and 1, 5–13, 1 mmHg for diastolic BPV, respectively. Despite similar levels of final BP, there were significant differences in mean BPV between groups: systolic BPV in group 1 was 7, 2 ± 3, 6 mmHg vs 7, 8 ± 6, 6 mmHg in group 2 and 10, 2 ± 3, 8 mmHg in group 3; diastolic BPV – 4, 8 ± 2, 7 mmHg vs 7, 0 ± 4, 4 mmHg and 7, 3 ± 2, 2 mmHg, respectively (p < 0, 01 for trend). No predictors of BPV were found in all groups. Conclusions: Despite similar BP levels HF with reduced EF is associated with the highest visit-to-visit BPV compared to uncomplicated AH and stable CHD. Thus high visit-to-visit BPV may be a marker of the severity of cardiovascular disease.